Mantle-Derived Helium Emission near the Pohang EGS Site, South Korea: Implications for Active Fault Distribution. (24th July 2020) - Kim, Heejun; Lee, Hyunwoo; Lee, Jaemin; Lee, Hyun A.; Woo, Nam Chil; Lee, Youn-Soo; Kagoshima, Takanori; Takahata, Naoto; Sano, Yuji
Abstract : An Mw 5.5 earthquake occurred in Pohang, South Korea on November 15, 2017, resulting in a great impact on society. Despite a lot of controversy about the cause of the earthquake in relation to the enhanced geothermal system (EGS), the location of earthquake-related active faults is poorly known. Here, we first report the results of the geochemical and isotopic analyses of dissolved gases in groundwater in the Heunghae, Yeonil, and Sinkwang areas. According to the N2 -Ar-He relationship, samples from the Heunghae and Yeonil areas are contributed to the mantle, except for the Sinkwang area, where all samples are atmospheric. The Pohang samples consist mainly of N2 and CO2, and some samples of the Heunghae and Yeonil areas contain substantial CH4 . Stable isotope compositions of N2 (δ 15 N = 0.2   to   3.6 ‰ ), CO2 (δ 13 C = − 27.3   to − 16.0 ‰ ), and CH4 (δ 13 C = − 76.1   to − 70.0 ‰ ) indicate that these components are derived from organic substances in sedimentary layer of Pohang Basin. On the other hand, helium isotope ratios ( 3 He/ 4 He, up to 3.83 Ra) represent the significant mantle contribution in the Heunghae and Yeonil areas. Through the distribution of high 3 He/ 4 He ratios, we propose that the Heunghae, Namsong, and Jamyeong faults are the passage of mantle-derived fluids. Computed 3 He fluxes of the Heunghae (120 to 3, 000 atoms cm -2  sec -1 ), Namsong (52 to 1, 300 atoms cm -2  sec -1 ), and Jamyeong (83 to 2, 100 atoms cm -2  sec -1 ) faults are comparable to other major active faults around the world, reflecting either high porosity or high helium flow rates. Therefore, our results demonstrate that there are active faults near the EGS facilities, which can provide the basis for future studies.